Particulate matter effect on biometric and biochemical attributes of fruiting plants - U. Younis; T.Z. Bokhari; S.A. Malik; M.H. Raza Shah; M. Athar; S. Niaz (Global Journal of Environmental Science and Management)
Dust accumulation capacity of Ficus carica L. and Psidium guajava L. was investigated from eight different sites of Multan, Pakistan.  Leaves of both plants were used for analyzing biometric (leaf area, fresh and dry weights) and biochemical attributes (chlorophyll contents, carotenoids and ascorbic acid).  Maximum dust accumulation was occurred in the plants growing near road sites, while, minimum dust accumulation occurred in the plants of Bahauddin Zakariya University.  Most of the biometric and biochemical attributes of F. carica showed significant response towards dust but it had not significant influence on some attributes of P. guajava.  Biochemical traits of P. guajava appeared to be more prone than foliage ones. A positive correlation was foundbetween dust accumulation and foliage attributes in F. carica. On the other hand,in P. guajava opposite was observed, however, the reverse was true for leaf biomass.Biochemical contents had shown an inconsistency as chlorophylls (a, b & total), carotenoid contents declined but ascorbic acid increased with an increase in dust accumulation in both species.